Penurunan COD dan TSS pada Limbah Greywater Menggunakan Metode Elektrokoagulasi: Indonesia - Munandar, Andika; Yanda, Rahma; Salsabila, Tarisya (Jurnal Sains & Teknologi Lingkungan, 2026)
Domestic activities at the ITERA TB 2 student dormitory generate greywater containing significant levels of Chemical Oxygen Demand (COD) and Total Suspended Solids (TSS), alongside specific pH levels. The direct discharge of this untreated wastewater poses a severe threat to local ecosystems. To address this issue, this study investigates electrocoagulation—an electrically-driven coagulation process—as an alternative treatment method to mitigate pollutant concentrations. The research evaluated the reduction of COD and TSS (dependent variables) across varying applied voltages (10, 20, and 30 V) and contact times (30, 60, and 90 minutes) as independent variables. The results indicated that the optimum treatment occurred at 30 V with a 90-minute contact time. Under these conditions, COD was successfully reduced from 115 mg/L to 11.5 mg/L, and TSS decreased from 103 mg/L to 9.5 mg/L, accompanied by a pH shift from 7.11 to 9.3. These findings demonstrate the efficacy of the electrocoagulation method in significantly reducing greywater pollutants.